Conchotome and needle percutaneous biopsy of skeletal muscle. Issue 11 (November 1987) - Dietrichson, P; Coakley, J; Smith, P E; Griffiths, R D; Helliwell, T R; Edwards, R H
Abstract : Percutaneous muscle biopsy is an important and acceptable technique in the study of conditions involving human skeletal muscle. A review of 436 conchotome and needle muscle biopsies obtained over 18 months in this centre is presented.